Violence at the Intersections of Women’s Lives in an Urban Context: Indigenous Women’s Experiences of Leaving and/or Staying With an Abusive Partner - Smye, Victoria (Violence against women, 2021)
This article is based on an ethnographic study exploring Indigenous women’s experiences of leaving intimate partner violence. Analysis draws attention to the contextual features of Indigenous women’s lives that differentially shaped women’s experiences of “leaving and/or staying” with an abusive partner. Our findings are identified and described across four intersecting thematic areas: (a) the context of state-Indigenous relations; (b) complex trauma, stigma, and discrimination; (c) kinship and ties to communities and the land; and (d) health, healing, and resistance. These findings offer valuable insights into what constitutes appropriate, safe services, and support for the Indigenous women whose lives are shaped by multiple forms of violence.